Inventário e avaliação da geodiversidade no município de Goiás e Parque Estadual da Serra Dourada - Pinto Filho, Ricardo de Faria (2014)
The term "geoconservation" is becoming popular within the academic community. The lack of academic studies makes the geoconservation theme doesn't diffuses in Brazilian territory. This dissertation have like study area for analysis of geoconservation's preservation, the city of Goias and State Park Serra Dourada. This paper aims is discuss the preservation of cultural, geological and ecological heritage of the region in the Serra Dourada; identify and inventory the geological heritage and historical sites that are relevant to mining; investigate under the geographical aspect of the geoconservation's functionality in the study area and to propose measures for the implementation of geotourism; map and record the geological heritage present in the studied region. Given the realization of the objectives proposed in the initial stage was a literature review on the state of the art related to aspects of geoconservation on physical geography and landscape, as well as a review of the historical appropriation of the study area. The dissertation also included field work to identify and do Georeferencing in geological, geomorphological and mining sites. The study found that the city of Goiás and Serra Dourada State Park has a great potential for practical of geotourism. This research identified 15 geosites of significant importance to the region. The analysis of data collected in the field concludes that the establishment of a geopark can be an important factor for the preservation and conservation of geological, geomorphological and mining heritage in the region.